Peningkatan Hasil Belajar IPAS Melalui Penerapan Model Problem Based Learning Bagi Siswa Kelas IV SD Negeri Yosodipuro Semester 1 Tahun 2022 - Minawati, Adik (Universitas Sebelas Maret, 2022)
The purpose of this research is to improve the learning outcomes of IPAS for fourth-grade students at Yosodipuro Elementary School. The target of the change is the students' participation and learning outcomes, with the action variable being the Problem-Based Learning model.The research takes the form of classroom action research with a cycle model. Each cycle consists of planning, implementing actions, observation, and reflection. The subjects of this study are fourth- grade students at Yosodipuro Elementary School, totaling 15 students. Data collection techniques include document analysis, testing techniques, field notes, observation, and motivation questionnaires. Data analysis uses an interactive analysis model consisting of data reduction, data presentation, and drawing conclusions.The research results show that the motivation percentage before the cycle was 65.2% (categorized as low motivation), and after the cycle, it became 82.1% (categorized as high motivation), showing an increase of 16.9%. This improvement is accompanied by the average class score in science subjects, which increased from 59.5 before the cycle to 85.2 after the cycle. Thus, teaching science with the Problem-Based Learning model can enhance the motivation for learning science for fourth-grade students at Yosodipuro Elementary School.